On the Role of Calcium-Permeable AMPARs in Long-Term Potentiation and Synaptic Tagging in the Rodent Hippocampus - Park, Pojeong; Kang, Heather; Sanderson, Thomas M.; Bortolotto, Zuner A.; Georgiou, John; Zhuo, Min; Kaang, Bong-Kiun; Collingridge, Graham L. (Frontiers in Synaptic Neuroscience, 2019)
Classically, long-term potentiation (LTP) at hippocampal CA1 synapses is triggered by the synaptic activation of NMDA receptors (NMDARs). More recently, it has been shown that calcium-permeable (CP)-AMPARs can also trigger synaptic plasticity at these synapses. Specifically, their activation is required for the PKA and protein synthesis dependent component of LTP that is typically induced by delivery of spaced trains of high frequency stimulation. Here we present new data that build upon these ideas, including the requirement for low frequency synaptic activation and NMDAR dependence. We also show that a spaced theta burst stimulation (sTBS) protocol induces a heterosynaptic potentiation of baseline responses via activation of CP-AMPARs. Finally, we present data that implicate CP-AMPARs in synaptic tagging and capture, a fundamental process that is associated with the protein synthesis-dependent component of LTP. We have studied how a sTBS can augment the level of LTP generated by a weak TBS (wTBS), delivered 30 min later to an independent input. We show that inhibition of CP-AMPARs during the sTBS eliminates, and that inhibition of CP-AMPARs during the wTBS reduces, this facilitation of LTP. These data suggest that CP-AMPARs are crucial for the protein synthesis-dependent component of LTP and its heterosynaptic nature.